Effect of glycyl-L-phenylalanine 2-naphthylamide on invertase endocytosed by rat liver. - Jadot, M (1985)
The release by glycyl-L-phenylalanine 2-naphthylamide (Gly-L-Phe-2-NNap) of endocytosed invertase associated with the MLP fraction (sum of the M, L and P fractions [de Duve, Pressman, Gianetto, Wattiaux & Appelmans (1955) Biochem. J. 63, 604-617]) of rat liver was investigated and compared with the release of cathepsin C. The percentage of invertase released increases with time after the enzyme injection, whereas the release of cathepsin C is not influenced by this treatment and corresponds to 85-90% of the total activity of the enzyme. It takes about 2h to attain a similar release of both enzymes. The quantity of invertase releasable or not by Gly-L-Phe-2-NNap was plotted against the time after the injection. Results agree well with the hypothesis that unreleasable invertase is associated with a pre-lysosomal compartment, whereas releasable invertase is present in lysosomes. A kinetic analysis indicates that invertase enters the pre-lysosomal compartment with a zero-order rate constant of 0.48 unit/min per g fresh wt., and leaves this compartment with a first-order rate constant of 0.042 min-1.